Monitoring versus prediction of the power of three different PV technologies in the coast of Lima-Peru - Calsi, B.X.; Conde, L.A.; Angulo, J.R.; Montes-Romero, J.; Guerra Torres, J.A.; de la Casa, J.; Töfflinger, J.A. (IOP Publishing, 2021)
This article presents the benefits of two simple analytical models for estimating the outdoor performance of three different photovoltaic technologies in Lima, Peru. The Osterwald and the constant fill factor models are implemented to estimate the maximum power delivered by three photovoltaic module technologies: aluminum back surface field, heterojunction with intrinsic thin-layer and amorphous/microcrystalline thin-film tandem. A 12-months experimental campaign is carried out through measurements of current-voltage curves, irradiance and module temperature. The results show that both models overestimate the modelled power when compared to the measured one. In order to correct the maximum power predicted by both models, a correction factor is introduced. This correction factor allows us to estimate losses and a respective effective nominal power to minimize the prediction error on a monthly and yearly basis. These parameters demonstrate a unique behavior for each technology during different months implying different seasonal impacts of the ambient variables on the module performance. The effectiveness of this correction factor is demonstrated through accuracy measures. It enables the photovoltaic power prediction with an error < 1% for the particular climate in Lima, Peru.
Keywords: Photovoltaic system; Irradiance; Power (physics); Environmental science; Maximum power principle; Computer science; Voltage; Statistics; Mathematics; Electrical engineering; Engineering; Optics; Physics; https://purl.org/pe-repo/ocde/ford#2.04.00